Proportioning of Lightweight Concrete by the Inclusions of Expanded Polystyrene Beads (EPS) and Foam Agent - Eethar T. Dawood; Ali J. Hamad (Tikrit Journal of Engineering Sciences, 2016)
This paper illustrates the performance of lightweight concrete using various amounts of expanded polystyrene beads (EPS) and different amounts of foam agent to produce lightweight concrete. The objective of this paper is to produce lightweight concrete with good workability and strength, by different mix proportion of foam agent (0.4, 0.6, 0.8, 1, 1.2 kg/m3) and varying water cement ratio (w/c) depending on the flow. Besides, various proportions using different percentages of EPS in order of volume fractions are used. The flow range used in the study is 110-130%. Each mix proportion is tested for compressive strength, modulus of rupture, density and voids ratio. The results gives acceptable ranges of strength for lightweight concrete produced by the inclusions of EPS beads and foam concrete. Therefore, the lightweight concrete produced in this work can be used for structural applications like multistory building frames, floors, bridges and prestressed or precast elements.